Analisis Pendapatan dan Kelayakan Usahatani Bawang Merah dengan Aplikasi Kompos Gapoktan “Bahagia Makmur” Desa Banjaratma, Bulakamba, Kabupaten Brebes - Juwanda, Muhammad; Melly Fera; Khusnul Khotimah; Reismaya Wanamertan Nugroho; Zulaikha Anugraheni (SINTA Journal (Science, Technology, and Agricultural), 2025)
Shallots are a highly sought-after vegetable commodity in Indonesia, particularly for household consumption as a flavoring agent. Analysis of income and feasibility of shallot farming in Banjaratma Village, Bulakamba District, Brebes Regency has never been studied. This study was conducted to determine the income analysis and feasibility of shallot farming conducted by farmers who are members of the "Bahagia Makmur" Farmers Group (Gapoktan) in Banjaratma Village, Bulakamba District, Brebes Regency. The location of Banjaratma Village was chosen purposively as the research location because farmers in the village consistently grow shallots throughout the year. The research method used is a qualitative method with a case study type. The data used are primary and secondary data. The shallot farming carried out by farmers is professional by applying shallot leaf compost as an additional organic material in the soil so that soil fertility in the area can be maintained. The income of shallot farmers also increased with the method of applying shallot leaf compost much better than using conventional methods that farmers usually do with an increase in income of 33.27%. The R/C ratio value is 2.51 for cultivation with compost and the R/C ratio value for cultivation without compost is 2.14 which is the basis that the shallot farming carried out by farmers who are members of the Bahagia Makmur Farmers Group, Banjaratma Village, Brebes Regency is feasible to be pursued. The application of shallot leaf compost technology to planting land really helps farmers in increasing shallot production by 18.24% compared to without compost.